Research in the history of economic thought and methodology. volume 41, including a selection of papers presented at the first History of Economics Diversity Caucus Conference - Fiorito, Luca; Scheall, Scott; Suprinyak, Carlos Eduardo (Research in the history of economic thought and methodology ;, 2023)
Research in the History of Economic Thought and Methodology Volume 41B features a selection of papers presented at the First History of Economics Diversity Caucus Conference, new research essays from Roger Sandilands and co-authors Daniel Schiffman and Eli Goldstein, as well as an interview of Francis Wilson conducted by Phil Magness and Micha Gartz.